The Comparison of Junior High School Student Comprehension about Slow Loris Conservation Based on Participation on Slow Loris Awareness Activity - Nurhayati, N; Sukandar, Paskal; Suryanda, Ade (Biosfer: Jurnal Pendidikan Biologi, 2014)
Slow loris are Indonesia’s primate that is protected and in threat. Slow loris existence in the nature are very thoughtful due to lack of habitat, illegal hunting, and illegal trading. This is because the lack of people awareness about slow loris existence so that it is necessary to held an activity that can improve conservation awareness like Slow Loris Awarenessthat held by Yayasan IAR (International Animal Rescue) Indonesia. The aim of this research was to know the comparison of junior high school student comprehension about slow loris conservation based on participation on Slow Loris Awareness activity. This research was conducted atjunior high school 14 of Jakarta on July 2012. The method of the research was quasi-experiment with nonrandomized control group, pretest-posttest design. The research sample was student of class VIII B and VIII D with 32 students each. The instruments that used were comprehension test question. The analysis prerequisite test was normal and homogen. This research showed that the average of pretest score for experiment class was 61,58 and postest score was 75,18, meanwhile the average of pretest score for control class was 63,05 and postest score was 68,38.The hypothesis was tested using t test showed reject H0, It could be conclude that the comprehension about slow loris conservation on junior high school students who participated in Slow Loris Awareness activity were better than students who did not participate.